A techno-economic assessment for fuel cells hybrid systems in stationary applications - Fontalvo Morales, Victor Manuel; Nelson, George J. J.; Pupo-Roncallo, Oscar; Sanjuan, Marco E. E.; Gomez, Humberto A. A. (My University, 2023)
This study evaluates the techno-economic feasibility of integrating fuel cells into stand-alone power generation systems, combined with different technologies such as diesel generators, wind turbines, and batteries. An optimisation analysis was performed using the Hybrid Optimization Model for Multiple Energy Resources (HOMER) software to minimise energy costs and several system architectures were obtained for different operating scenarios. The performance and cash flow of the selected system were included. The results suggest that the combination of traditional technologies for fuel cell power generation could be feasible for a country like Colombia, depending on economic factors such as the Consumer Price Index (CPI), the discount rate, and the availability of renewable resources. The proposed system achieves a Levelized Cost of Electricity (LCOE) of $0.112/kWh, comparable to state-of-the-art systems in the literature. This research contributes to the global effort of transitioning to alternative energy sources and reducing carbon emissions.
Keywords: hybrid energy systems; optimisation; homer; renewable energy; hydrogen; fuel cells